2018
DOI: 10.1108/jamr-09-2017-0086
|View full text |Cite
|
Sign up to set email alerts
|

Performance management model for teachers based on emotional intelligence and social media competencies

Abstract: Purpose The technological advances worldwide are posing challenges for the teaching fraternity. However, certain competencies can enable the teachers to enhance their performance by managing self and adopting flexible teaching and learning tools. The purpose of this paper is to identify, analyse and model such competencies with special reference to emotional intelligence and social media competencies (SMCs). A competency framework is developed and a subsequent performance ranking system is derived in this stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 31 publications
0
9
0
Order By: Relevance
“…This study determines the meaningful relations based on the synthesized theoretical framework. Prior work in a similar area has been focused on advanced countries (Nelis et al, 2011 ; Kaur et al, 2018 ; Li and Xu, 2019 ), while very few studies have been conducted in emerging nations like China (Maguire et al, 2017 ; Li and Xu, 2019 ). Moreover, these limited studies have revealed a lack of attention to the curriculum contents in blended learning while paying more attention to the substantial roles for efficient use of resources in blended education.…”
Section: Discussionmentioning
confidence: 99%
“…This study determines the meaningful relations based on the synthesized theoretical framework. Prior work in a similar area has been focused on advanced countries (Nelis et al, 2011 ; Kaur et al, 2018 ; Li and Xu, 2019 ), while very few studies have been conducted in emerging nations like China (Maguire et al, 2017 ; Li and Xu, 2019 ). Moreover, these limited studies have revealed a lack of attention to the curriculum contents in blended learning while paying more attention to the substantial roles for efficient use of resources in blended education.…”
Section: Discussionmentioning
confidence: 99%
“…Given the immense rise in users of social media platforms and subsequent rise in user-generated content, social media analytics analyzes communication pattern and behavior in relation to external phenomenon (Hidayat et al, 2019;Garg et al, 2019;Sobti, 2019;Cao et al, 2018;Dlamini and Johnston, 2018;Kaur et al, 2018;Stieglitz et al, 2018;Gandomi and Haider, 2015), thus investigating trends and patterns (Boyd and Ellison, 2007). In particular, Twitter is considered to be a gold mine of data which provides a rich source of information about the business performance and serves as a low-cost marketing medium (Malhotra et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…The performance management system should include measures synced with company strategies and provide diverse and balanced support. Plenty of research evident relation of employee performance with various factors like employees' perceptions of diversity within management levels (Kundu et al , 2019), Succession plan, staffing plan and talent management strategies (Chakraborty and Biswas, 2019), internal communication and reward and recognition (Ali et al , 2019), organizational citizenship behavior (OCB), leader–member exchange (LMX), learning, innovative work behavior (IWB) (Atatsi, 2019), impact of various competencies (Kaur et al , 2018). However, several challenges are associated with most desired performance expectations.…”
Section: Literature Reviewmentioning
confidence: 99%